LECTURERS APPLICATION DATA ADMINISTRATION SYSTEM. JAKARTA STMIK STI & K USING MICROSOFT VISUAL FOXPRO 9.0 - Achmad Sarif; Yudi Irawan Chandra, Skom, MMSI Yudi Irawan Chandra, Skom, MMSI (Jurnal Sistem Informasi, 2010)
Scientific writing is about an Administration Application Data STMIK Lecturer STI& K. Jakarta This application was created to provide information on faculty data,which can facilitate data searches lecturer at STMIK STI & K. Jakarta.In scientific writing, the Application for Data Administration Lecturer authors makeuse Microsoft Visual FoxPro 9.0 that can provide ease in searching and security instoring data for the user STMIK Administration STI & K. Jakarta.